Características morfológicas e químicas de plantas de cajueiro (Anacardium occidentale L.) associadas à resistência da mosca-branca-do-cajueiro - Mateus, Antônio Edgar (2017)
In the Northeast region of Brazil, a cashew is characterized as one of the most important sources of employment and income. Among the main problems that reduce the potential of the crop is the cashew whitefly, Aleurodicus cocois (Curtis, 1846) (Hemiptera: Aleyrodidade), which is found widespread in all producing regions in Brazil. To minimize the impacts of the pest, pesticides have been used erroneously, which increases the risk of developing pest resistance. Thus, the need for research that seeks the development of control methods that offer a practical and safe solution is emphasized. In this way, the objective was to study the morphological and chemical resistance in clones of cashew-dwarf in front of the attack of A. cocois. The resistance to field conditions (Experimental field in Pacajus-CE) for 10 clones and laboratory conditions for clones CCP 76 and PRO 143/7. There was among the clones the infestation of the cashew white fly in the field. For the color of the abaxial face of the leaves, only the clones 143/7 and 131/2 presented a green color (value 1), the other clones presented a dark green color (value 2), occurred between the thickness and the size of the leaves, the however Leaf size was not a characteristic that influenced the degree of pest infestation. The CCP 76 clone was detached, as it releases more volatile compounds than clone PRO 143/7. The α-pinene and β-myrene compounds were more liberated in the CCP 76 clones, said to be susceptible to cashew whitefly attack. A coloring and leaf thickness of dwarf cashew clones are morphological characters that confer resistance to A. cocois. Significant qualitative or quantitative presentations among the volatile compounds released by the dwarf cashew clones, being α-pinene and β-myrene produced only by the CCP 76 clones, yet produced to a greater extent when they are not infested and the volatiles emitted by the CCP 76 clones exert an attractive effect on A. cocois.